Collapsed cone dose calculations for heterogeneous tissues in brachytherapy using primary and scatter separation source data. (February 2017) - Ahnesjö, Anders; van Veelen, Bob; Tedgren, Åsa Carlsson
Highlights: The manuscript reports details of a computing methodology for brachytherapy dose calculation. Brachytherapy is a form of radiotherapy using small, sealed radioactive sources. The computational method described in this manuscript is, since 2014, available in a commercial software for radiation treatment planning from Elekta AB (Stockholm, Sweden). Elekta's soft- and hardware for brachytherapy is developed and manufactured in Veenendal, the Netherlands (earlier under the name Nucletron) and is a large distributor of brachytherapy equipment (hard- and software). The performance of the software described here has been validated earlier in the literature, however, the implementation details presented in the current manuscript have not been published before nor sent for publication anywhere else. The comprehensive description and derivations provided give a rigid background for further clinical, educational and research applications. Abstract: Background and Objective: Brachytherapy is a form of radiation therapy using sealed radiation sources inserted within or in the vicinity of the tumor of, e.g., gynecological, prostate or head- and neck cancers. Accurate dose calculation is a crucial part of the treatment planning. Several reviews have called for clinical software with model-based algorithms that better take into account the effects of patient individual distribution of tissues, source-channel and shielding attenuation than the commonly employed TG-43 formalism which simply map homogeneous water dose distributions onto the patient. In this paper we give a comprehensive and thorough derivation of such an algorithm based on collapsed cone point-kernel superposition, and describe details of its implementation into a commercial treatment planning system for clinical use. Methods: A brachytherapy version of the collapsed-cone algorithm using analytical raytraces of the primary photon radiation followed by successive scattering dose calculation for once- and multiply scattered photons is described in detail, including derivation of the corresponding set of recursive equations for energy transport along cone axes/transport lines and the coupling to clinical source modeling. Specific implementation issues for setting up of the calculation grid, handling of intravoxel gradients and voxels partly containing non-patient applicator material are given. Results: Sample runs for two clinical cases are shown, one being a gynecological application with a tungsten-shielded applicator and one a breast implant. These two cases demonstrate the impact of improved dose calculation versus TG-43 formalism. Conclusions: Use of model-based dose calculation algorithms for brachytherapy taking the three-dimensional treatment geometry into account increases the dosimetric accuracy in planning and follow up of treatments. The comprehensive description and derivations provided gives a rigid background for further clinical, educational and research applications.